DESAIN TAMPILAN ANTARMUKA PELAPORAN EKSTERNAL DATA KEGIATAN PELAYANAN (RL5) RUMAH SAKIT AKADEMIK UGM KEPADA DINAS KESEHATAN PROVINSI YOGYAKARTA - , FAJAR ESRI ARFIANTI; , Nur Rokhman, S.Si., M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background of the problems: The developments of Science and Technology have cleared away in many fields including the healthy field. This progress gives a change for parties which understand with this change, so, be born the Electronic Medical Record. The computer electronic radiologyâs activities give many positive effects such as the ease of the data presentation so that, the giving information will be effective and efficient. Based on the observation, it found that the Academic Hospital of Gajah Mada University (UGM) has used the Electronic Medical Record. The processing and recording of the patientsâ data had been implemented computerized. However, the external reporting activity in reporting the hospital servicing data activities (RL5) was still manually. Objective: designing the preview of hospital servicing data activities (RL5) which is appropriate with the usersâ need so that it helps the official in reporting the external report. Method: the design started with doing observation then, wrote the all activities that happened. The observation was done in Academic Hospital Gajah Mada University especially in Electronic Medical Record. Another method was done by interviewing the resource persons. They were reporting official, the head of Electronic Medical Record installation and Informative technology official. Findings: the finding of this design was the interface preview in reporting the servicing hospital data activities (RL5) was appropriate with usersâ need in Academic Hospital of Gajah Mada University (UGM). This preview helped the Electronic Medical Record official in reporting the external reportâs activities.